TEAMWORKING IN HOSPITAL INSTITUTIONS: AN INTEGRATIVE REVISION - Silvia Henriques Camelo (Universidade Federal do Paraná, 2011)
A present-day hospital is an organization for providing health services, where knowledge, health service professionals, technology, and a wide variety of infrastructure come together. Team-working is a strategy which aims at linking the actions and knowledge of the diverse health professionals inserted in this environment, promoting the integrality of care. This article aimed to contextualize the modality of teamwork with a caring dimension in a hospital institution. It is an integrative revision carried out by consulting the electronic databases Lilacs and SciELO; the bibliographic survey was effected between the months of August and November 2010. The results showed that hospitals present a structure with a vertical hierarchy and fragmentation of responsibilities. Teamwork is used to take on the process of specialization and occasion the opportunity to construct a global vision of each situation, through communication between the professionals involved in the therapeutic process.